Penerapan Media Pembelajaran E-Modul Pada Materi Geometri Bidang Ruang Untuk Meningkatkan Kompetensi Guru Matematika Kelas XII MAN 1 Ambon - Haris Kolengsusu (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the application of e-module learning media to geometry material in the field of space to increase the competency of class XII mathematics teachers MAN 1 Ambon. The method in this study is a quasi-experimental method (quasi experimental). This research was carried out at MAN 1 Ambon and the subjects in the study were math teachers who taught class XII. Items are made in the form of multiple choices. The preparation of the items is guided by the revised Bloom's taxonomy. Instrument trials were conducted on 2 teachers of MAN 1 Central Maluku, to obtain validity, reliability, difficulty index and item discriminating power using the multiple choice ANOTES program version 4.0.9. From the results of the test questions, it was found that there were 30 valid questions with a reliability coefficient of 0.75, this means that the instrument used is classified as having high reliability. The value of mastery of the teacher's concept in the experimental group and the comparison group after learning has increased. The mean was then tested using the Kolgorov-Smirnov test to determine population distribution, from the output obtained Kolgorov-Smirnov Z in the experimental group 0.669 and the comparison group 0.749 and the significance 0.761 and 0.628 because the significance > 0.05 it was concluded that the data were normally distributed. The data was then tested with levene to see the sample distribution, the test results obtained a significance value of 0.07. the significance value was > 0.05 so that the sample distribution was concluded to be not homogeneous so it was tested with the Mann-Whytney U test to see the level of significance of differences in mastery of concepts between study groups. The test results obtained Asym sig significance. 0.11 and Exact sig. 0.11. because the significance is > 0.05, it can be concluded that learning geometry in the field of space using e-modules can significantly improve the teacher's mastery of concepts compared to learning using printed media e-modules.